Principal Leadership Strategies for Enhancing Teacher Motivation in Rural Elementary Education: A Qualitative Study - Da’im Da’im; Yasir Arafat; Muhammad Juliansyah Putra (Journal of Social Work and Science Education, 2026)
This study examines principal leadership strategies for enhancing teacher motivation in a rural elementary school setting, specifically addressing the contextual challenges of resource-limited environments. Using a descriptive qualitative approach, the research was conducted at SDN 6 Empat Petulai Dangku, Muara Enim Regency, South Sumatra. Participants included the principal, supervisor, teachers, students, committee representatives, and administrative staff, selected via purposive sampling. Data were collected through interviews, observation, and documentation, then analyzed using data reduction, display, and conclusion drawing, with trustworthiness ensured through source and technique triangulation. Findings reveal that the principal strengthened teacher motivation through participatory planning, academic supervision, professional development, appreciation, discipline coaching, and supportive communication. However, major obstacles persisted, including limited facilities, uneven teacher discipline, low digital competence, heavy administrative loads, and scarce external support. This study offers a contextualized leadership model tailored to rural Indonesian elementary schools, integrating instructional, democratic, and emotional dimensions rarely combined in prior research. The results underscore the need for district policymakers to provide targeted infrastructure, digital training, and workload relief to complement school-level leadership efforts. This research contributes empirical evidence that effective rural principalship demands a balanced synthesis of instructional guidance, participative decision-making, emotional support, and strategic resource optimization to sustain teacher motivation and elevate learning quality despite geographical and infrastructural constraints.